Study of Problems and Solutions in Human Resource Management in Thailand in 21st Century: A non-systematic literature review method - Phasansinthuwong, Aree; Someran, Laddawan; Kerdngern, Nopphong; Joungtrakul, Jamnean (Journal of Humanities and Social Sciences Thonburi University, 2024)
This academic paper aims to study (1) concepts and model in human resource management, (2) the factors that impact on human resource management in Thailand in the 21st century, and (3) the problems and solutions in human resources management in Thailand in the 21st century. A non-systematic literature review method was applied in this study from articles related to human resource management in Thailand, published in journals indexed by the Thai Journal Citation Index (TCI) between the years 2018-2022. The sample selection involved a combination of purposive sampling and convenient sampling, resulting in the inclusion of 20 articles for analysis. The study reveals that human resource management originated from the guild system and evolved into Human Resource Management (HRM), with the potential transition to Human Capital Management (HCM) in the future. The human resource management model can be divided into four components: input factors, operational processes, internal organizational outcomes, and organizational returns. Concerning the impact on human resource management in Thailand in the 21st century, it can be categorized into two aspects: external and internal situations. In the section addressing the problems and solutions in human resource management in Thailand in the 21st century, five key areas are identified: human resource planning, recruitment and selection, training and development, performance evaluation and compensation, and labor relations. These areas encompass the challenges and potential solutions for effectively managing human resources in the Thai context.